Zdrowie własnej rodziny w świetle opinii włoskich i polskich uczniów = The opinions of Italian and Polish students on their families' health - Marianna Charzyńska-Gula; Magdalena Gębka; Hanna Kachaniuk; Agnieszka Szymczak; Beata Zięba-Kołodziej (Kazimierz Wielki University, 2016)
Charzyńska-Gula Marianna, Gębka Magdalena, Kachaniuk Hanna, Szymczak Agnieszka, Zięba-Kołodziej Beata. Zdrowie własnej rodziny w świetle opinii włoskich i polskich uczniów = The opinions of Italian and Polish students on their families' health. Journal of Education, Health and Sport. 2016;6(8):54-66. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.59744 http://ojs.ukw.edu.pl/index.php/johs/article/view/3727       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016.     Zdrowie własnej rodziny w świetle opinii włoskich i polskich uczniów The opinions of Italian and Polish students on their families' health   Marianna Charzyńska-Gula 1, Magdalena Gębka 2, Hanna Kachaniuk 3, Agnieszka Szymczak 2, Beata Zięba-Kołodziej 1   1 Państwowa Wyższa Szkoła Zawodowa im. prof. Stanisława Tarnowskiego w Tarnobrzegu/Professor Stanisław Tarnowski State Higher Vocational School in Tarnobrzeg 2 Samodzielny Publiczny Szpital Kliniczny nr 4 w Lublinie/ Independent Public Teaching Hospital No. 4 in Lublin 3 Katedra Onkologii i Środowiskowej Opieki Zdrowotnej Uniwersytet Medyczny w Lublinie/Department of Oncology and Community Health Care, Medical University of Lublin     Streszczenie      Rodzina jest dla dziecka miejscem "tworzenia się zdrowia" w największym stopniu zaspokajającym  jego psychospołeczne potrzeby  i dającym początek najwcześniejszym przyzwyczajeniom i nawykom  wypełniającym później pro- lub anty-zdrowotny styl życia.      Celem badań było poznanie opinii na temat zdrowia własnej rodziny wyrażanych przez włoskich i polskich uczniów i ustalenie, na ile wybrane cechy społeczno-demograficzne oraz zachowania zdrowotne członków tych rodzin wiążą się ze stosunkiem uczniów do zadania, jakim jest dbałość o zdrowie przez całe życie.             Badano 175 uczniów (90 z Polski i 85 z Włoch (średnia wieku 16,95 lat). Zastosowano sondaż diagnostyczny z autorskim kwestionariuszem ankiety. Badania prowadzono w Polsce i Włoszech w okresie od marca 2014 do marca 2015 roku.      Wyniki wskazują na brak związku między wybranymi cechami rodzin a świadomością zdrowotną uczniów. Włoscy rodzice, mimo, że są lepiej wykształceni od polskich częściej palą tytoń, a ich dzieci wyraźnie częściej niż ich rówieśnicy z Polski nie widzą potrzeby dbania o zdrowie przez całe życie.  Polscy rodzice mimo słabszego wykształcenia, rzadziej są osobami palącymi tytoń i ich dzieci znacząco częściej, niż włoscy rówieśnicy mają właściwy stosunek do dbałości o zdrowie.      Uzyskane dane wskazują na różną w obu społecznościach  aktywność szkół w działaniach profilaktycznych, która mogła wypełniać luki rodzinnej edukacji na rzecz zdrowia.   Słowa kluczowe: zdrowie rodziny, zachowania zdrowotne, uczeń.   Abstract             For children family is a source of health; it meets their psychosocial needs and shapes their earliest habits, which later can turn into a healthy or unhealthy lifestyle.             The objectives of the study was to identify the opinions of Italian and Polish students on their families' health and to determine the extent to which selected socio-demographic characteristics and health behaviour of the analysed families are related to the students' attitude towards the duty of caring for their health throughout their lives. The surveyed group included 175 students (90 from Poland and 85 from Italy (average age: 16.95 years). The diagnostic survey method was applied, with the use of a self-designed questionnaire. The surveys were carried out in Poland and Italy from March 2014 to March 2015.             The results point to the lack of correlation between the selected characteristics of the analysed families and the students' health awareness. Italian parents, despite their higher education in comparison to Polish parents, more often smoke tobacco and are more frequently unable to assess their body weight. Their children substantially more often than their peers from Poland do not consider it necessary to care for their health throughout their lives. Polish parents, in spite of having lower education, less frequently smoke tobacco. Their children significantly more often than their Italian peers have an appropriate attitude to caring for their health.             The obtained data show differences observed in both communities in the activity of schools in terms of prophylactic measures, which could fill the gaps in family health education.   Key words: family's health, health behaviour, student.